The Characteristics Variation of Hepatic Progenitors after TGF-β1-Induced Transition and EGF-Induced Reversion - Ping Wang; Min Cong; Tianhui Liu; Aiting Yang; Guangyong Sun; Dong Zhang; Jian Huang; Shujie Sun; Jia Mao; Hong Ma; Jidong Jia; Hong You (Stem Cells International)
Profibrogenesis cytokine, transforming growth factor- (TGF-) β1, induces hepatic progenitors experiencing epithelial to mesenchymal transition (EMT) to matrix synthesis cells, even tumor initiating cells. Our previous data found that epidermal growth factor (EGF) blocks and reverses TGF-β1-induced transition. The aim of this study is to determine the characteristic changes of hepatic progenitors after TGF-β1-induced transition and EGF-induced reversion. Hepatic oval cells, rat hepatic progenitors, were isolated from rats fed a choline-deficient diet supplemented with ethionine. TGF-β1-containing medium was used for inducing EMT, while EGF-containing medium was used for reversing EMT. During TGF-β1-induced transition and EGF-induced reversion, hepatic oval cells sustained their progenitor cell marker expression, including α-fetoprotein, albumin, and cytokeratin-19. The proliferation ability and differentiation potential of these cells were suppressed by TGF-β1, while EGF resumed these capacities to the level similar to the control cells. RNA microarray analysis showed that most of the genes with significant changes after TGF-β1 incubation were recovered by EGF. Signal pathway analysis revealed that TGF-β1 impaired the pathways of cell cycle and cytochrome P450 detoxification, and EGF reverted TGF-β1 effects through activating MAPK and PI3K-Akt pathway. EGF reverses the characteristics impaired by TGF-β1 in hepatic oval cells, serving as a protective cytokine to hepatic progenitors.